THE RELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE: A MODERATE ROLE OF FINANCIAL TECHNOLOGY - Dika Fuji Okta; Stefani Darmawan; Rimi Gusliana Mais (Bajang Institute, 2024)
This research aims to explain the relationship between company’s financial performance and corporate social responsibility in the development of financial technology. The method in this research is using a qualitative approach with a literature review method where the data is obtained from relevant secondary data such as trusted journal articles. The results of this research illustrate that financial technology helps company to carry out their social responsibilities, especially in the current digital economic era. Social responsibility that runs well will also improve the performance of the company itself. Although this research is only limited to relevant journal articles, it does not rule out the possibility of collecting other data to support this research. To sum up, integrating corporate social responsibility and financial technology not only has a big impact on society but also improves company’s financial performance.